Efeitos do envelhecimento e da atividade física regular em índices da variabilidade da freqüência cardíaca e da arritmia sinusal respiratória de homens saudáveis - Melo, Ruth Caldeira de (Universidade Federal de São Carlos, 2004)
The purpose of the present study was to evaluate the effects of the aging and the regular physical activity on the autonomic control of heart rate (HR) at rest and during deep breath test (DBT) in healthy men. Nine young sedentary (mean = 22.67 ±2.45 years), sixteen young active (mean = 22.38 ±2.13 years), eight sedentary older (mean = 63.5 ±2.39 years) and eight older active (mean = 61 ±1.6 years) men were studied. Electrocardiogram was continuously recorded during 15 minutes (rest), 4 minutes (DBT, with breath rate at 5 to 6 cycles/minute) and 1 minute (recovery) in supine position. The HR (bpm) and the R-R intervals (RRi) (ms) were analyzed by time (RMSSD index) and frequency domain methods. The power spectral components were expressed as absolute (a) and normalized units (nu) at low (LF) and high (HF), and as the LF/HF. The HR and the RRi were analyzed by the respiratory sinus arrhythmia (RSA) indices: expiration/inspiration ratio (E/I) and inspiration-expiration difference (∆IE). The HR was lower in the activity groups than to the matched-age sedentary groups. The older sedentary group had lower heart rate variability (HRV), E/I and ∆IE than young ones. The older active group showed higher RMSSD and HF component than matched-age sedentary group (45.04 and 28.78 ms, 58,167 and 12,218 ms2/Hz, P<0.05; respectively). No differences were found between young and older active groups for RMSSD (61.71 and 45.04 ms, respectively) and HRV (TP:130,816 and 125,710, LFa:33,295 and 32,611, HFa:84,346 and 58,167, ms2/Hz, respectively) and DBT indices (E/I: 1.40 and 1.35, ∆IE: 23 and 18, respectively). The results show that aging associates with inactivity reduces the HRV. However, the regular physical activity increases the HRV, independent of age, suggesting attenuation the effects of the aging in the autonomic control of the heart rate.
Effects of aging and physical activity on indices of the heart rate variability and respiratory sinus arrhythmia in healthy men
Keywords: Fisiologia do exercício físico; Variabilidade da freqüência cardíaca; Arritmia sinusal respiratória; Sistema nervoso autônomo; Envelhecimento; Heart rate variability; Respiratory sinus arrhythmia; Autonomic nervous system; Aging process; Regular physical activity; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL